More citizenship, less party politics” : the ambivalent dynamics of political activism in Luanda - (:unkn) unknown (My University, 2023)
Panel Poli24 : "Trials and transformations : the futures of citizenship in Africa".In August 2017, José Eduardo dos Santos steps down from the Angolan Presidency after 38 years. Incoming President João Lourenço surprises everyone by promising to open a dialogue with civil society and to implement a national struggle against corruption. For the handful of activists who had taken the streets and suffered harsh repression under dos Santos, it is the beginning of a new era. Street mobilisations and acephalous networks give way to more formal organisations. The network “Jovens Pelas Autarquias” (Youth for Municipalisation) becomes a channel for an unprecedented campaign that brings together lobbying activities directed to Members of Parliament on the one hand, and work of popular political education in various urban communities across the city on the other hand.By unraveling both the rhetoric and the actions of three different collectives affiliated to this network, the paper shows the emergence of an unprecedented sense of political community that effectively disrupts the old binarity of Angolan party politics. But it also points to the fragility of these initiatives. They often reproduce a political imagination marked by the hierarchy between board-members and foot-soldiers, between the intellectuals and the masses, and even between those who belong to state-institutions and those who navigate in the margins of the state.Exploring these tensions sheds new light on the ambivalent dynamic of democratization from below and questions the theoretical vulnerability of the concept of citizenship, seen here both as a demand for accountability and as a tool of disciplinarisation of popular politics.
Keywords: African Research